New species of Aberrapex Jensen, 2001 (Cestoda: Lecanicephalidea) from eagle rays of the genus Myliobatis Cuvier (Myliobatiformes: Myliobatidae) from off Argentina - Menoret, Adriana (2017)
Three new species of Aberrapex Jensen, 2001 (Cestoda, Lecanicephalidea) have been collected from species of Myliobatis Cuvier along the coast of Argentina. Aberrapex ludmilae sp. n. parasitizes M. goodei Garman in the San Matías Gulf. This species is unique in a combination of features including the shape and extent of the uterus, scolex size, testis distribution, and by lacking an external seminal vesicle and postovarian vitelline follicles. Aberrapex sanmartini sp. n., from M. goodei in San Blas Bay, and A. vitalemuttiorum sp. n. from M. ridens Ruocco, Lucifora, Díaz de Astarloa, Mabragaña et Delpiani in coastal waters off Buenos Aires Province, are distinguished from all other congeners by the microthrix pattern on the scolex surface, uterus shape and extension, position of the connection of the uterine duct to the uterus, presence and extension of an external seminal vesicle, and its overall size and number of proglottids. The specimens of M. goodei and M. ridens show locally distinct cestode faunas, which are correlated with well-defined biogeographic regions. Some of these areas correspond with mating and nursery zones for species of Myliobatis.